Causative Microorganisms of Infectious Endophthalmitis: A 5-Year Retrospective Study - Fang Duan; Kaili Wu; Jingyu Liao; Yongxin Zheng; Zhaohui Yuan; Junlian Tan; Xiaofeng Lin (Journal of Ophthalmology)
This study aimed to identify the microbial etiology of infectious endophthalmitis and to determine the antibacterial susceptibilities of bacterial isolates at an eye hospital in South China. A retrospective analysis was carried out on 330 patients with clinically diagnosed infectious endophthalmitis who underwent microbiological evaluation from January 2010 to December 2014. Of the 330 patients, 193 patients (58.5%) had posttraumatic endophthalmitis, 67 patients (20.3%) had postoperative endophthalmitis, 61 patients (18.5%) had endogenous endophthalmitis, and 9 patients (2.7%) had postcorneal infective endophthalmitis. Of the 105 cases (31.8%) of culture-positive endophthalmitis, 79 cases (75.2%) had bacterial growth and 26 cases (24.8%) had fungal growth. In posttraumatic endophthalmitis, Gram-positive bacteria were the predominant species, followed by Gram-negative bacteria and fungi. In endogenous endophthalmitis, Gram-negative bacteria were the predominant species, followed by fungi and Gram-positive bacteria. In postsurgical endophthalmitis, all infections were bacterial. However, in postcorneal infective endophthalmitis, all infections were fungal. Overall, levofloxacin showed the highest activity against bacterial isolates. There was a significant difference in the susceptibility to tobramycin between the isolates from posttraumatic and postoperative endophthalmitis (p<0.05). The results of this study identify the microbial spectrum of infectious endophthalmitis in this clinical setting.